NuclampFISH enables cell sorting based on nuclear RNA expression for chromatin analysis - Yifang Liu; Yuchen Qiu; Keqing Nian; Sara H. Rouhanifard (BMC Genomics)
Abstract Background Transcriptional bursts are periods when RNA polymerase interacts with a DNA locus, leading to active gene transcription. This bursting activity can vary across individual cells, and analyzing the differences in transcription sites can help identify key drivers of gene expression for a specific target RNA. Scaffolding methods based on fluorescence in situ hybridization (FISH) have been widely used to amplify the fluorescent signal of RNAs and sort cells based on RNA expression levels. Examples include click-amplifying FISH (clampFISH) and hybridization chain reaction (HCR). However, these methods are limited in their ability to target and amplify transcription sites, due to the long probes’ hindered accessibility through cellular compartment membranes and crosslinked proteins. Thus, sorting based on transcriptional bursting has not been achieved. Additionally, the required formaldehyde fixation interferes with downstream analysis of chromatin and protein-binding interactions. Results To address these challenges, we developed a platform, nuclear clampFISH (nuclampFISH) that integrates click-amplified FISH with reversible crosslinkers and allows access to the nucleus. We demonstrate that with optimized parameters and by eliminating the cytosol and cell membrane, this method enables the amplification of fluorescent signal for RNAs using a reversible crosslinker, enabling the sorting of cells based on nuclear RNA expression and is compatible with downstream biochemical analysis including chromatin conformation assays. We applied this assay to demonstrate that transcriptionally active cells have more accessible chromatin for a respective gene. Conclusions This new method enables the sorting of cells based on transcriptional bursts. This method combines the specificity of a single-cell assay for detecting transcription sites with the throughput of flow cytometry to enable bulk assays such as chromatin conformation or other biochemical assays. Notably, the tools developed are highly accessible and do not require specialized computation or equipment.